Recurrence of a t(8;21)-Positive Acute Myeloid Leukemia in the Form of a Granulocytic Sarcoma Involving Cranial Bones: A Diagnostic and Therapeutic Challenge. (11th September 2013) - Di Veroli, Ambra; Micarelli, Alessandro; Cefalo, Mariagiovanna; Ceresoli, Eleonora; Nasso, Daniela; Cicconi, Laura; Mauramati, Simone; Ottaviani, Fabrizio; Venditti, Adriano; Amadori, Sergio
Abstract : Granulocytic sarcoma (GS) is a rare extramedullary solid tumor defined as an accumulation of myeloblasts or immature myeloid cells. It can cooccur with or precede the acute myeloid leukemia (AML) as well as following treated AML. The incidence of GS in AML patients is 3–8% but it significantly rises in M2 FAB subtype AML. This variety of AML harbors t(8;21) in up to 20–25% of cases (especially in children and black ones of African origin) and, at a molecular level, it is characterized by the generation of a fusion gene known as RUNX1-RUNX1T1. Approximately 10% of M2 AML patients will develop GS, as a consequence, the t(8;21) and the relative transcript represent the most common cytogenetic and molecular abnormalities in GS. FLT3-ITD mutation was rarely described in AML patients presenting with GS. FLT3 ITD is generally strongly associated with poor prognosis in AML, and is rarely reported in patients with t(8;21). GS presentation is extremely variable depending on organs involved; in general, cranial bones and sinus are very rarely affected sites. We report a rare case of GS occurring as a recurrence of a previously treated t(8;21), FLT3-ITD positive AML, involving mastoid bones and paravertebral tissues.